The Infuence of Cash Flow Information Toward Stock Return - Reza Kurniawan (International Conference On Law, Business and Governance (ICon-LBG), 2013)
The purpose statement of cash flows is to provide relevant information on the revenues and expenditures of a company in a period. This information is useful to investors and creditors to assess a companys ability to generate future net cash flows and compare them with short-term liabilities and long-term, including the possibility of future dividend payments. On the other hand also represents the value of the stock value of the company, not just an intrinsic value at a time, but more importantly it represents hope in the ability of the company in the future. Therefore, the purpose of this study was to examine the effect of cash flow information either partially or simultaneously on the companys stock return.